A plain-image correlative semi-selective medical image encryption algorithm using enhanced 2D-logistic map - Bahbibi Rahmatullah (Tanjung Malim, 2023)
A plain-image correlative semi-selective medical image encryption algorithm using enhanced 2D-logistic map by Bahbibi Rahmatullah